PERBANDINGAN RERATA BESARAN LEEWAY SPACE SUKU BANJAR DENGAN RERATA LEEWAY SPACE MENURUT PROFFIT (Studi Analitik Observasional Radiograf! Periapikal pada Masa Gigi Bercampur) - Gusti Meidy L; Fajar Kusuma D.K; Irnamanda D.H. (Odonto : Dental Journal, 2016)
Background: Leeway space is an excess space available because of the differences between the amount of mesiodistal width of canine, first premolar and second premolar and the amount of mesiodistal width of primary canine, first molar and second molar. There's a variation of Leeway space among individuals. This variation occurs because of growth and development period which are influenced by environmental factors, nutrition and ethnic variations. Purpose: The purpose of this study was to determine the difference in the average Leeway space of Banjarese population with the size of Leeway space according to Proffit.Method: This study used an observational analytic with cross sectional approach. The number of mesiodistal width of primary c, m1, and m2 is substracted with the number of mesiodistal width of permanent C, P1, and P2 of 77 samples to determine the average Leeway space and then compared with the Leeway space according to Proffit. Measurements were done using a digital caliper followed with data analysis using Mann-Whitney test.Result: The average of Banjarese population Leeway space is 0.37 mm in each region of the maxilla and 2.2 mm in each region of the mandible. Results of the Mann-Whitney test showed that there were significant differences in maxillary Leeway space of Banjarese population compared to the Leeway space according to Proffit.Conclusion: The conclusion of this study is there were differences between the average Leeway space of Banjarese population with the Leeway space according to Proffit.